"Knowledge migrants" or "economic migrants"? Patterns of academic mobility and migration from Southern Europe to Mexico. Issue 2 (16th November 2019) - Mendoza, Cristóbal; Staniscia, Barbara; Ortiz, Anna
Abstract: Because mobility has been described as a key element of the academic habitus and a well‐established norm in scientific life, people moving within academia have been generally considered to be "knowledge migrants" and "talent migrants." Indeed, the literature rarely takes a labour market perspective when analysing academic mobility. However, Southern European academia is largely characterised by challenging working conditions, low wages, and a lack of fair competition for positons, all of which negatively affecting job prospects. Based on 25 in‐depth interviews, this paper explores the reasons behind the migration of a group of Spanish and Italian academics in Mexico with a view to bringing into focus the role of economic/labour and career‐related reasons in migration decisions. We find that their experiences fall along three main academic trajectories, which are distinguished by the stage in the participants' careers at which they decided to migrate and the channels by which they entered Mexican academia. Common to all three groups is the identification of the economic crisis and a lack of institutional support as strong motivating factors in their decision. Underlying this is the question of whether the studied group is best viewed as "knowledge"/"talent" migrants who have followed certain institutional channels or "economic migrants" who are somehow pushed to work abroad by the lack of good employment in their countries of origin. The paper also challenges mainstream ideas about academic mobility, in the sense that the literature has not considered the attractive power of universities/research centres located in the Global South.